2008
DOI: 10.1105/tpc.107.053926
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana Type I Isopentenyl Diphosphate Isomerases Are Targeted to Multiple Subcellular Compartments and Have Overlapping Functions in Isoprenoid Biosynthesis

Abstract: To form the building blocks of isoprenoids, isopentenyl diphosphate (IPP) isomerase activity, which converts IPP to dimethylallyl diphosphate (DMAPP), appears to be necessary in cytosol, plastids, and mitochondria. Arabidopsis thaliana contains only two IPP isomerases (Isopentenyl Diphosphate Isomerase1 [IDI1] and IDI2). Both encode proteins with N-terminal extensions similar to transit peptides and are expressed in all organs, with IDI1 less abundant than IDI2. Examination of enhanced green fluorescent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 69 publications
3
105
0
1
Order By: Relevance
“…Unlike the MEP pathway enzymes, IDI is encoded by two genes in Arabidopsis, IPI1/IPPI1/IDI1 (At5g16440) and IPI2/IPPI2/IDI2 (At3g02780). Although the simultaneous production of both IPP and DMAPP by the MEP pathway is expected to make the presence of a plastidial IDI activity dispensable, both IDI1 and IDI2 isoforms have been found in chloroplasts by using GFP fusions and proteomic approaches, the latter suggesting the presence of IDI1 in the stroma and IDI2 in membranes (Phillips et al, 2008a;Sapir-Mir et al, 2008;Joyard et al, 2009). A plastidial isomerase might ensure that an appropriate ratio between IPP and DMAPP is maintained for isoprenoid biosynthesis.…”
Section: Mep Pathway To Ggppmentioning
confidence: 99%
“…Unlike the MEP pathway enzymes, IDI is encoded by two genes in Arabidopsis, IPI1/IPPI1/IDI1 (At5g16440) and IPI2/IPPI2/IDI2 (At3g02780). Although the simultaneous production of both IPP and DMAPP by the MEP pathway is expected to make the presence of a plastidial IDI activity dispensable, both IDI1 and IDI2 isoforms have been found in chloroplasts by using GFP fusions and proteomic approaches, the latter suggesting the presence of IDI1 in the stroma and IDI2 in membranes (Phillips et al, 2008a;Sapir-Mir et al, 2008;Joyard et al, 2009). A plastidial isomerase might ensure that an appropriate ratio between IPP and DMAPP is maintained for isoprenoid biosynthesis.…”
Section: Mep Pathway To Ggppmentioning
confidence: 99%
“…Metabolic flux through these pathways can differ dramatically, and the flux through the MEP pathway often exceeds that of the MVA (McCaskill and Croteau, 1995;Dudareva et al, 2005;Wu et al, 2006). It was reported that IPP and perhaps DMAPP could be exchanged between different compartments, particularly in the direction from plastids to cytosol (Hemmerlin et al, 2003;Laule et al, 2003;Schuhr et al, 2003;Dudareva et al, 2005;Phillips et al, 2008), raising a question about the relative contribution of each pathway to the biosynthesis of the various classes of terpenoids. Trafficking of isoprenoid intermediates between organelles, likely mediated by specific metabolite transporters (Bick and Lange, 2003), depends on the plant species, tissue, and physiological state of the plant (Steliopoulos et al, 2002;Dudareva et al, 2005;Hampel et al, 2005aHampel et al, , 2005b.…”
Section: Introductionmentioning
confidence: 99%
“…Most plants have two copies of ippi (Table 1), which are thought to have specialised but overlapping functions (Cunningham and Gantt 2000;Nakamura et al 2001;Okada et al 2008;Phillips et al 2008). In Arabidopsis, one copy is expressed more strongly in the cytosol (termed idi2) and the other more strongly in the plastid (termed idi1).…”
Section: Downstream Of Ippmentioning
confidence: 99%
“…In Arabidopsis, one copy is expressed more strongly in the cytosol (termed idi2) and the other more strongly in the plastid (termed idi1). However, knockouts mutants of each gene in Arabidopsis have shown that each idi gene can compensate for the other in both parts of the cell and that there is no significant difference in terpenes produced or growth phenotypes by either idi1 or idi2 knockouts when compared to the wild type (Okada et al 2008;Phillips et al 2008). IPP and DMAPP form the backbone of all plant terpenes, apart from isoprene which is synthesized directly from IPP and the ratio of IPP : DMAPP is thought to be important in allocating resources to the synthesis of the different classes of terpene.…”
Section: Downstream Of Ippmentioning
confidence: 99%
See 1 more Smart Citation